The Implementation of Google Sheets–Assisted Guided Discovery Learning to Analyze Students’ Interest and Learning Outcomes in the Basic Laws of Chemistry - Thomas Calvin Andjasmara; Sri Susilogati (Jurnal Inovasi Pendidikan Kimia, 2025)
This study aimed to analyze the implementation of Guided Discovery Learning (GDL) assisted by Google Sheets in exploring students’ interest and learning outcomes on the Basic Laws of Chemistry for 11th-grade students. The research was conducted at senior high school in Semarang, involving 45 students from classes XI Fearless and XI Genuine, selected using convenience sampling. An explanatory sequential design was employed, beginning with quantitative data collection on students’ learning outcomes and interest in chemistry, followed by qualitative interviews to explain unexpected findings. Descriptive analysis showed that students’ average interest score was 96.13 (75%), with the highest indicator being “students’ attitude toward assigned tasks” (81%) and the lowest being “independent awareness in learning chemistry” (47%). Knowledge outcomes averaged 54.67, with only 5 students surpassing the Minimum Mastery Criteria. The affective dimension revealed higher achievement, particularly in levels A1 (receiving, 78%) and A3 (valuing, 76%). Critical thinking skills remained low, with 73% of students categorized as “very low.” Interviews indicated that difficulties in understanding material, preference for conventional learning, and external factors contributed to the gap between high interest and low learning outcomes. These findings suggest that while GDL assisted by Google Sheets effectively enhances students’ interest, additional instructional support and reinforcement are necessary to translate high interest into improved learning achievement